Calibration of a concentration-driven nucleation mechanism for phase-field simulations of eutectic and off-eutectic compositions in AlCu-5Ag. (September 2020) - Hinrichs, Frauke; Kellner, Michael; Hötzer, Johannes; Nestler, Britta
Graphical abstract: Abstract: The present work is an extension of the studies conducted by Kellner et al. [M. Kellner et al., Acta Materialia, vol. 182, pp 267–277, 2020.], to show the transferability of their concentration-driven nucleation mechanism to other systems. The implementation of this method improves the adjustment process of directionally solidifying eutectic structures in two-dimensional phase-field simulations. To quantitatively evaluate the nucleation mechanism, the velocity-spacing relationships of different eutectic and off-eutectic melt compositions are investigated for AlCu-5Ag . A good agreement between simulations with and without the nucleation mechanism is found for all studied compositions.